Study of Capacity Calsium Board – Styrofoam Sandwich Panels on Wall Systems under Cyclic Lateral Force - Fatriady, M. R.; Djamaluddin, Rudy; Tjaronge, Muhammad Wihadi; Amiruddin, Andi Arwin (Engineering, Technology & Applied Science Research, 2024)
A new type of lightweight shear wall has been developed using composite panels, with styrofoam as the core layer and calcium board as the skin layer. This innovation aims to facilitate the rapid construction of housing in response to earthquake disasters. Physical testing of the material showed an increase in the compressive strength of the styrofoam core, from 2.14 MPa to 3.74 MPa in 75 mm thick sandwich panels. This study examines the use of precast panels with specific installation techniques involving pick-up beams (sloofs), connectors, and panel to panel connections to enhance wall strength against horizontal earthquake loads. The conducted cyclic loading test followed the ASTM E2126-18 (2018) standard loading cycle pattern test method. Lateral force experiments were conducted on full-scale shear walls with two different panel-frame connection modes. The test results revealed the behavior of Panel Lightweight Concrete (PLC) walls under cyclic lateral forces. Combined wall panels acted independently, and the use of PVAc adhesive and steel connectors resulted in a unified wall behavior system. The displacement behavior of the wall within the pinch system in the notch on the sloof demonstrated positive results. Quipanel walls can reduce building weight, mitigate earthquake forces, and provide a robust structure capable of withstanding long-term lateral forces. This development leads to the construction of simple, earthquake-resistant houses.